2001
DOI: 10.1073/pnas.121046998
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a hormonally regulated rat long chain acyl-CoA synthetase

Abstract: L uteinizing hormone (LH) supports steroidogenesis and maintains testicular and ovarian function (1). Mediators of LH action exert homologous regulation of receptors, steroidogenic enzymes, and other genes of the Leydig cell. In contrast to the physiological concentrations of gonadotropins that maintain steroidogenesis and gonadal LH͞human chorionic gonadotropin (hCG) and prolactin receptors, high exogenous concentrations of hCG down-regulate receptors and steroidogenic enzymes of Leydig cells at steps beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 29 publications
(64 reference statements)
6
59
0
Order By: Relevance
“…However, our IMS data suggest ACSL- (19 -48) to be present at the periphery of seminiferous tubules. This is in accordance with previous work showing that the protein is expressed in Leydig cells and to a lesser extent in Sertoli cells and spermatogonia (53). In the rat testis, Leydig cells are isolated or clustered into small groups throughout the interstitial compartment.…”
Section: -M Maldi Imaging Of Spermatogenesissupporting
confidence: 80%
See 1 more Smart Citation
“…However, our IMS data suggest ACSL- (19 -48) to be present at the periphery of seminiferous tubules. This is in accordance with previous work showing that the protein is expressed in Leydig cells and to a lesser extent in Sertoli cells and spermatogonia (53). In the rat testis, Leydig cells are isolated or clustered into small groups throughout the interstitial compartment.…”
Section: -M Maldi Imaging Of Spermatogenesissupporting
confidence: 80%
“…The corresponding 79-kDa cytoplasmic progenitor protein is expressed in rodent gonads and brain. In the testis, it may participate in steroidogenesis and, through the multiple functions of acyl-CoA, in the regulation of the male gonad (53). This is another example for the ability of the top-down imaging strategy to specifically detect and identify …”
Section: -M Maldi Imaging Of Spermatogenesismentioning
confidence: 99%
“…The testicular cell-specific and hormonal-dependent usage of translation codons for GRTH protein synthesis add complexity and diversity to regulatory mechanism(s) that may participate during testicular development. The up-regulation of GRTH protein by gonadotropin in the Leydig cells follows closely the down-regulation of receptors, steroidogenic enzymes, and acyl-CoA synthetase (gonadotropin-regulated long chain acyl-CoA synthetase) (4,23), and its return to control levels is concomitant to its recovery from down-regulation. These changes could be reflective of the existence of a regulated mechanism responsible for recovery of down-regulated transcriptional events through increases in translatability of the reduced relevant messages.…”
Section: Discussionmentioning
confidence: 99%
“…14 C]Palmitic acid (C16:0), [1-14 C]arachidonic acid (C20:4), [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]docosahexaenoic acid (C22:6), and [1-14 C]lignoceric acid (C24:0) were obtained from Moravek, Inc. [1-14 C]Myristic acid (C14:0), [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]stearic acid (C18:0), [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]oleic acid (C18:1), and [1][2][3][4][5][6][7]…”
Section: Materials and General Methods-[1-mentioning
confidence: 99%
“…Subsequently, Moriya-Sato et al (7) reported that in the mouse, BG1 was expressed in adrenal gland and testis as well and Tang et al (8) noted that rat BG1 was also expressed in ovary. A Northern blot prepared using total RNA from tissues of 3-month-old 129SvEv mice and probed with an mBG1-specific probe indicated that mBG1 was expressed in brain, adrenal gland, testis, ovary, and spleen ( Fig.…”
Section: Substrate Specificity Of Hbg1 Expressed In Cos-1 Cells-mentioning
confidence: 99%